Does monetary policy generate recessions? - Christopher A. Sims; Tao A. Zha (Federal Reserve Bank of Atlanta, 1998)
The issue of uncovering the effects of monetary policy is far short of resolution. In the identified VAR literature, restrictions have been imposed to identify the effects of unpredictable monetary policy disturbances. We offer critical views on the unreasonable assumptions in the existing work and argue for careful economic argument about identifying assumptions. We display a structural stochastic equilibrium model in which our VAR identification would produce correct results while drawing attention to the serious lack of time series fit in most of the DSGE literature.
Keywords: 330; Monetary policy